Thru‐reflect‐line calibration for substrate integrated waveguide devices with tapered microstrip transitions. Issue 2 (1st January 2013) - Caballero, E. Diaz; Belenguer, A.; Esteban, H.; Boria, V.E.
Abstract : One of the main problems when exciting or measuring substrate integrated waveguide (SIW) devices lies in the need of a good interconnection with planar structures. In this reported work, the negative effects produced by the connectors and the tapered microstrip‐to‐SIW transitions are de‐embedded from the measurements of the SIW structure by a thru‐reflect‐line calibration with an adequate and cheap SIW calibration kit.